#### Answer

$z=\dfrac{7}{6}$

#### Work Step by Step

Using the properties of equality, the solution to the given equation, $
2z-5+3z=4-(z+2)
$ is
\begin{array}{l}\require{cancel}
2z-5+3z=4-z-2
\\\\
2z+3z+z=4-2+5
\\\\
6z=7
\\\\
z=\dfrac{7}{6}
.\end{array}

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$z=\dfrac{7}{6}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.